(untitled) (Journal of actual problems of jurisprudence, 2019)
In this article the author tries to reveal the globalization processes, and only some of the dangerous challenges and threats of the twenty-first century. It is noted that in this sense, the twentieth century marked the beginning of the transition to a new era, but it appears the fatal end of the fork, when humanity must find answers to the challenges of the coming century. Every strategy begins with an assessment of threats, so you should properly assess the threat.